Exploring Sustainability Risks in Circular Manufacturing: Concept and Future Research - Syahrullah Yudi; Ciptomulyono Udisubakti; Dewi Ratna Sari (E3S Web of Conferences)
Manufacturing is the third largest contributor to greenhouse gas emissions in the world. Exploration of resources to produce raw materials is one process that contributes to greenhouse gas emissions. Using recycled materials in manufacturing with the circular economy principle is one way to reduce the carbon footprint. However, the application of the principle of a circular economy has various challenges and risks. Therefore, sustainability risks in circular manufacturing need to be developed and studied in more depth. This research was conducted using bibliometric analysis using R Software and literature review analysis. The results of the bibliometric analysis produced three research clusters that showed new potential with topics that could be collaborated on. Research on circular business models and risks is still rarely developed but has a high level of relevance, so it still has the potential to be developed. The literature review results strengthen the bibliometric analysis findings by creating a study on sustainability risks in circular manufacturing, the recycling industry, and other recovery industries. Research that examines the impact of sustainability risks on circular manufacturing that processes solid waste can be recommended in further research.